Horizon - Taylor, Dick (United States : BBC Active, 2006)
This program advocates a different approach, creating an array of unusual challenges to assess brainpower and positing an argument for the interplay of multiple intelligences
Editor, Andrew Cohen ; sound, Simon Farmer, Dave Calvert ; camera, Colin Rogal, Guy Linton, Peter Thorm
Narrated by Mark Halliley ; test subjects: Bonnie Greer, Nathan Haselbauer, Seth Lloyd, Susan Polgar, Alex Prior, Garry Stratford, Stella Vine
Keywords: Multiple intelligences; Learning, Psychology of; Intelligence tests; Learning